2012
DOI: 10.1007/s00404-012-2279-5
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase activity in patients with ovarian neoplasms

Abstract: Serum and peritoneal fluid ADA levels were found to be higher in malignant ovarian neoplasms. This finding may be useful to understand the biochemically characteristics of malignant ovarian tumors and ADA may be a useful biomarker in diagnosis and management of ovarian tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…Several studies investigated the change of the adenosine deaminase activity in various cancerous patients. Many authors have shown the increase of serum tADA activity in these patients (4,7,(23)(24)(25)(26). Adapted to previous data, our results showed higher ADA activity in patients with lung cancer compared to controls.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Several studies investigated the change of the adenosine deaminase activity in various cancerous patients. Many authors have shown the increase of serum tADA activity in these patients (4,7,(23)(24)(25)(26). Adapted to previous data, our results showed higher ADA activity in patients with lung cancer compared to controls.…”
Section: Discussionsupporting
confidence: 85%
“…In an attempt to describe human lung cancer, many studies have concentrated on enzyme activities (3)(4)(5). In addition, some studies established alteration of enzyme activity in bronchoalveolar lavage (6,7). To better understand purine enzymology in lung cancer, more attention has been paid to the investigation of the interrelationship among the carcinogenic process and enzyme activity (de novo and salvage pathways) for purine biosynthesis (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations